Optimization of Liquid Shampoo Formula from Chia Seed Oil (Salvia hispanica L) Using the Simplex Lattice Design Method - Amalina, Faidatul; Rahmayanti, Mayu; Afrizal, Muhammad; Nastiti, Ginanjar Putri; Syarifuddin, Sadli (Media Farmasi: Jurnal Ilmu Farmasi, 2024)
Hair is one of the most essential parts of the human body, both men and women; one of the problems with hair that often occurs is hair loss. Chia plants contain sebum gland-stimulating agents with a keratin protein concentration of 23%. The sebaceous glands play a role in facilitating the growth of hair follicles so that hair can thrive and prevent hair loss. This research aims to determine the optimum composition of the prediction formula using Design Expert software and the physical characteristics and stability of liquid shampoo preparations. Optimization was carried out using Design Expert 13 software with two material components, namely HPMC and SLS, and two responses, namely viscosity and foam height. The optimum formula obtained was subjected to characteristic tests and stability tests. The stability test was carried out using the cycling test method by storing the preparation at temperatures of 4◦C and 40◦C for 48 hours. The results of the prediction formula show that component X1 is 0.589307% and X2 is 9.41069%. The one-sample t-test showed that the results were not significantly different at p>0.05 in the two responses. Testing of the optimum formula's physical characteristics and physical stability meets the reasonable requirements for organoleptic tests, homogeneity tests, viscosity tests 414,80±9,94 cPs, foam height tests 7,060±0,11 cm, and pH tests 7,39±0. The 8th run is the optimum formula with a composition of X1 0.589307% and X2 9.41069 % meets the requirements for good physical characteristics tests and physical stability tests.